2015
DOI: 10.7773/cm.v41i2.2484
|View full text |Cite
|
Sign up to set email alerts
|

Water–air carbon fluxes in the coastal upwelling zone off northern Baja California

Abstract: M C INTRODUCTIONA topic of great concern and interest for climatologists and oceanographers is to determine how quickly natural and anthropogenic CO 2 is being absorbed by the oceans. The ocean acts as a large CO 2 sink (Takahashi et al. 2009), and a better understanding of the actual rate of ocean uptake of INTRODUCCIÓNUno de los temas más críticos y de gran interés para climatólogos y oceanólogos es conocer qué tan rápido está siendo absorbido el CO 2 natural y antropogénico por el océano. Dado que el océano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
4
0
5
Order By: Relevance
“…This region features strong upwelling events with low SST (<14 ºC), relatively low salinity (<34.0), and high pCO 2W values (~700 atm), resulting in an export of excess CO 2 to the atmosphere. By contrast, Muñoz-Anderson et al (2015) reported that during the weak upwelling season, it is characterized by intermediate surface temperatures and low pCO 2W values (down to ~300 µatm), resulting in a CO 2 sink. These authors used a MAPCO 2 system to analyze the seasonal changes of pCO 2W and FCO 2 in one year (2009), without any reference to high frequencies (i.e., diurnal changes) or interannual changes.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…This region features strong upwelling events with low SST (<14 ºC), relatively low salinity (<34.0), and high pCO 2W values (~700 atm), resulting in an export of excess CO 2 to the atmosphere. By contrast, Muñoz-Anderson et al (2015) reported that during the weak upwelling season, it is characterized by intermediate surface temperatures and low pCO 2W values (down to ~300 µatm), resulting in a CO 2 sink. These authors used a MAPCO 2 system to analyze the seasonal changes of pCO 2W and FCO 2 in one year (2009), without any reference to high frequencies (i.e., diurnal changes) or interannual changes.…”
Section: Introductionmentioning
confidence: 93%
“…Diferentes estudios han caracterizado las aguas costeras del Sistema de la Corriente de California usando distintas metodologías para definir su papel como fuente o sumidero de carbono (DeGrandpe et al 1998;Friederich et al 2002;Chávez et al 2007;De La Cruz-Orozco et al 2010;Pennington et al 2010;Evans et al 2011Evans et al , 2015Hales et al 2012;Fiechter et al 2014;Turi et al 2014;Muñoz-Anderson et al 2015;Mariano-Matías et al 2016). Sin embargo, hay incertidumbre en la dirección de FCO 2 en este sistema.…”
Section: Introductionunclassified
See 3 more Smart Citations